Information profession and professionals in 2011 - Tejada-Artigas, Carlos (Anuario ThinkEPI, 2012)
An overview is given of the profession of Information and Documentation in 2011. The economic crisis was the main factor that determined professional development and the labour market. Some of the key reports that have been outlined in social networks and blogs are also described.
Keywords: Profession; Professionals; Labour market; Library and information science; LIS.